2022
DOI: 10.1186/s12889-022-14045-4
|View full text |Cite
|
Sign up to set email alerts
|

“You can’t swim well if there is a weight dragging you down”: cross-sectional study of intimate partner violence, sexual assault and child abuse prevalence against Australian nurses, midwives and carers

Abstract: Background Domestic and family violence (DFV), including intimate partner violence (IPV), sexual assault and child abuse are prevalent health and social issues, often precipitating contact with health services. Nurses, midwives and carers are frontline responders to women and children who have experienced violence, with some research suggesting that health professionals themselves may report a higher incidence of IPV in their personal lives compared to the community. This paper reports the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…20 A limited body of empirical investigations have examined the incidence of IPV within the nursing population, the factors contributing to it, and its consequences. [20][21][22] However, research exploring the impact of psychological resilience on female nurses experiencing IPV, the extent of their work thriving, and the concomitant issue of work alienation remains scarce. This paucity of evidence impedes our ability to develop effective, evidence-based approaches to bolster work resilience among nurses.…”
Section: The Effect Of Psychological Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…20 A limited body of empirical investigations have examined the incidence of IPV within the nursing population, the factors contributing to it, and its consequences. [20][21][22] However, research exploring the impact of psychological resilience on female nurses experiencing IPV, the extent of their work thriving, and the concomitant issue of work alienation remains scarce. This paucity of evidence impedes our ability to develop effective, evidence-based approaches to bolster work resilience among nurses.…”
Section: The Effect Of Psychological Resiliencementioning
confidence: 99%
“…Gender roles, in traditional Chinese culture, males are often seen as the primary breadwinners and authoritative figures in the family, while females are expected to take on more household responsibilities. 22 These gender role stereotypes may contribute to power imbalances in intimate partner relationships, increasing the likelihood of violence. 23 Social pressure, Chinese society places high expectations on marriage and family, which may create significant pressure for individuals facing marital issues.…”
Section: Ipv Under the Background Of Chinese Female Nursesmentioning
confidence: 99%
“…Additionally, homicide against physician assistants has been shown to be commonly perpetrated by an intimate partner [14]. An Australian study [11] found that rates of IPV against nurses and midwives were higher than the general population. Giglio et al [5] surveyed orthopaedic surgeons and trainees about experiences of violence, but they only focused on workplace violence.…”
Section: Upon Closer Inspectionmentioning
confidence: 99%